Efferocytosis of apoptotic alveolar epithelial cells is sufficient to initiate lung fibrosis. Issue 11 (November 2018) - Kim, Kevin; Dotson, Megan; Agarwal, Manisha; Yang, Jibing; Bradley, Patrick; Subbotina, Natalia; Osterholzer, John; Sisson, Thomas
Abstract Type II alveolar epithelial cell (AEC) apoptosis is a prominent feature of fibrotic lung diseases and animal models of pulmonary fibrosis. While there is growing recognition of the importance of AEC injury and apoptosis as a causal factor in fibrosis, the underlying mechanisms that link these processes remain unknown. We have previously shown that targeting the type II alveolar epithelium for injury by repetitively administering diphtheria toxin to transgenic mice expressing the diphtheria toxin receptor off of the surfactant protein C promoter (SPC-DTR) develop lung fibrosis, confirming that AEC injury is sufficient to cause fibrosis. In the present study, we find that SPC-DTR mice develop increased activation of caspase 3/7 after initiation of diphtheria toxin treatment consistent with apoptosis within AECs. We also find evidence of efferocytosis, the uptake of apoptotic cells, by alveolar macrophages in this model. To determine the importance of efferocytosis in lung fibrosis, we treated cultured alveolar macrophages with apoptotic type II AECs and found that the uptake induced pro-fibrotic gene expression. We also found that the repetitive intrapulmonary administration of apoptotic type II AEC or MLE-12 cells induces lung fibrosis. Finally, mice lacking a key efferocytosis receptor, CD36, developed attenuated fibrosis in response to apoptotic MLE-12 cells. Collectively, these studies support a novel mechanism linking AEC apoptosis with macrophage pro-fibrotic activation via efferocytosis and reveal previously unrecognized therapeutic targets.